3D Printing of Customized Carbon Microneedle Arrays - Ren, Ya; Zhang, Li; Zhou, Angxi; Ma, Donglin; Liu, Haofan; Tian, Run; Wang, Siyi; Yang, Chunli; Gou, Maling (MedComm - Biomaterials and applications, 2025)
ABSTRACT Microneedles have gained considerable attention as an emerging technology in tissue regeneration, drug delivery, and biosensing due to their minimally invasive nature and efficient therapeutic potential. Carbon, with its superior properties compared to polymers, ceramics, and metals, is an excellent candidate for microneedle fabrication. However, conventional carbon material fabrication methods often lead to defects such as structural deformation, cracking, and foaming, which hinder the development of high‐performance carbon microneedle arrays. To address these challenges, this study presents a precise, efficient, and cost‐effective manufacturing strategy that integrates 3D printing with pyrolysis. By designing a polymer precursor with a uniform mesh structure, we successfully developed structurally intact microneedles with significantly improved overall performance. The fabricated carbon microneedles demonstrated reliable mechanical strength, high electrical conductivity, favorable photothermal properties, and excellent biocompatibility. These characteristics suggest broad potential applications in various fields. Furthermore, this study provides valuable insights into the development of carbon microneedle fabrication, offering a viable pathway for large‐scale production and clinical translation. This work lays the foundation for advancing the technology and product development of carbon microneedle arrays while expanding their practical applications across the biomedical and healthcare sectors. Schematic diagram of the preparation process for carbon microneedle arrays.